Even moderate nutrient enrichment negatively adds up to global climate change effects on a habitat‐forming seaweed system. (27th June 2016) - Werner, Franziska Julie; Graiff, Angelika; Matthiessen, Birte
Abstract: Coastal marine ecosystems have been under high anthropogenic pressure and it can be assumed that prevalent local perturbation interacts with rising global stressors under proceeding climate change. Understanding their effective pathways and cumulative effects is of high relevance not only with regard to future risk assessment, but also for current ecosystem management. In benthic mesocosms, we factorially tested the effects of one global (combined elevated seawater temperature and CO2 concentration) and one local (nutrient enrichment) stressor on a common coastal Baltic seaweed system ( Fucus vesiculosus ). Both treatments in combination had additive negative impacts on the seaweed—epiphyte—mesograzer system by altering its regulatory mechanisms. That is, warming decreased the biomass of two mesograzer species (weakened top‐down control), whereas moderate nutrient enrichment increased epiphyte biomass (intensified bottom‐up control), which ultimately resulted in a significant biomass reduction of the foundation seaweed. Our results suggest that climate change impacts might be underestimated if local pressures are disregarded. Furthermore, they give implication for local ecological management as the mitigation of local perturbation may limit climate change impacts on marine ecosystems.